Performance & grading Pattern of serving low-priced Airlines - Chowdhury, Anil Bikas Kumar (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
Objective: To establish a resolution on the accomplishment of the economical airways with a view to help the aviation industry in framing strategies about such airlines.Methodology - Data have been procured from DGCA, India website. Here, the yearly data of each of the airlines have been utilized. The duration of sampling includes six years 2006-07 to 2011-12 taken for the purpose of classification of operating economical airlines in India. The empirical analysis has been performed on the basis of Discriminant Analysis (DA) using SPSS version 16.0.Findings - The model has classified 22 (87.5%) cases accurately out of 24 cases which is considerably large; hence, the model can be justified as a sound one.Impact - The work will help one perceive the key areas of strength and accordingly frame feasible strategies in order to improve performance.